2021
DOI: 10.1016/j.envres.2021.111749
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater monitoring as a supplementary surveillance tool for capturing SARS-COV-2 community spread. A case study in two Greek municipalities

Abstract: A pilot study was conducted from late October 2020 until mid-April 2021, aiming to examine the association between SARS-CoV-2 RNA concentrations in untreated wastewater and recorded COVID-19 cases in two Greek municipalities. A population of Random Forest and Linear Regression Machine Learning models was trained and evaluated incorporating the concentrations of SARS-CoV-2 RNA in 111 wastewater samples collected from the inlets of two Wastewater Treatment Plants, along with physicochemical parameters of the was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Although ANN or other machine learning models hold great promise for their application in WBE, only one previous study compared the effectiveness of random forest method with linear regression ( Koureas et al, 2021 ). The study focused on case numbers and both methods provide very high-level accuracy, likely due to the small dataset obtained from two WWTPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ANN or other machine learning models hold great promise for their application in WBE, only one previous study compared the effectiveness of random forest method with linear regression ( Koureas et al, 2021 ). The study focused on case numbers and both methods provide very high-level accuracy, likely due to the small dataset obtained from two WWTPs.…”
Section: Resultsmentioning
confidence: 99%
“…The applications of machine learning and artificial intelligent for the COVID-19 pandemic were reviewed for their potentials in treatment, medication, screening, prediction, forecasting, contact tracing, clinical trials, and drug/vaccination process ( Lalmuanawma et al, 2020 ; Mottaqi et al, 2021 ). A recent study used random forest method to predict the daily COVID-19 cases based on square root of viral concentration in wastewater, with or without normalization to chemical oxygen demand, for two wastewater treatment plants ( Koureas et al, 2021 ). The machine learning models showed improvement in comparison to linear regression models, which also have high correlation coefficients between wastewater measurements and cumulative cases around 0.8-0.9 in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reporting results for multi‐seasonal monitoring that occurred during periods of higher COVID‐19 testing include data from twice weekly sampling at nine wastewater treatment plants (WWTPs) in Ohio (Ai et al, 2021 ), once to five times weekly sampling at 12 WWTPs in Wisconsin (Feng et al, 2021 ), daily sampling at three WWTPs in Nevada (Li et al, 2022 ), and daily sampling at one WWTP in Greece (Galani et al, 2022 ), sampling two WWTPs in Greece (Koureas et al, 2021 ) and Argentina (Barrios et al, 2021 ; Giraud‐Billoud et al, 2021 ). These studies have reported correlations with reported daily cases (Ai et al, 2021 ; Feng et al, 2021 ) as well as rolling averages of 3–7 days (Ai et al, 2021 ), and cumulative cases for 7–20 days (Barrios et al, 2021 ; Koureas et al, 2021 ) in the sewer catchments. The correlations observed were generally consistent across WWTP; however, Feng et al ( 2021 ) noted that one WWTP had weaker correlations with reported cases and different catchment demographics (lower income, student population) were considered a potential explanation.…”
Section: Introductionmentioning
confidence: 99%
“…While sewer systems are being used as a tool for WBE, these systems were designed to meet other goals (e.g., sanitation and hydraulics) and present multiple challenges when it comes to interpretation of results. Perhaps best studied are methods for normalizing SARS‐CoV‐2 gene copies in sewage to other system flow, fecal viruses (Ai et al, 2021 ; Barrios et al, 2021 ; Feng et al, 2021 ; Wu et al, 2020 ), fecal indicators (Feng et al, 2021 ), and water quality indicators (Koureas et al, 2021 ) to help account for dilution in these systems that collect more than feces and urine. Among the studies that spanned more than one season (i.e., at least 5 months) reported to date, a variety of correlations between wastewater virus concentrations and clinical cases have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation